2017
DOI: 10.1086/689870
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in the Phenotypic Flexibility of Basal Metabolic Rate in Siberian Hamsters Are Consistent on Short- and Long-Term Timescales

Abstract: Basal metabolic rate (BMR) correlates with the cost of life in endothermic animals. It usually differs consistently among individuals in a population, but it may be adjusted in response to predictable or unpredictable changes in the environment. The phenotypic flexibility of BMR is considered an adaptation to living in a stochastic environment; however, whether it is also repeatable it is still unexplored. Assuming that variations in phenotypic flexibility are evolutionarily important, we hypothesized that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…developmental plasticity) can generate variation among individuals (Arnqvist et al 2010, Latimer et al 2011. Moreover, these determinants are likely to involve changes in biological traits of individuals such as body mass, which is generally responsible for a large amount of the variation in cellular metabolic activities (Boratynski et al 2017). Here, we found that the repeatability of the metabolic expression level (i.e.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…developmental plasticity) can generate variation among individuals (Arnqvist et al 2010, Latimer et al 2011. Moreover, these determinants are likely to involve changes in biological traits of individuals such as body mass, which is generally responsible for a large amount of the variation in cellular metabolic activities (Boratynski et al 2017). Here, we found that the repeatability of the metabolic expression level (i.e.…”
Section: Discussionmentioning
confidence: 63%
“…Moreover, body mass variation among individuals may play an important role in the evolutionary response to warming as larger individuals have higher metabolic expression level (i.e. intercept) than smaller ones (Boratynski et al 2017). We may thus predict a positive selection for small individuals having a lower expression level and 'slow type' individuals being less sensitive to warming.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, thyroid hormones could enable adaptive physiological responses to environmental and seasonal change. Here, we refer to any physiological adjustment of an organism in response to an environmental stimulus resulting in the improved ability of that organism to cope with its changing environment as physiological adaptation (Boratynski et al, 2017;Brinkmann et al, 2014;Rymer et al, 2016). However, physiological adaptation is also often called acclimatization (Noakes et al, 2017;Petit et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Here we suggest that plasticity of thermal performance curves is an ancestral trait that has been maintained in endotherms to buffer physiological reaction rates from variation in core body or tissue temperatures. Note that there is an important distinction between acclimation of metabolic rates to increase heat production in response to cold environmental temperatures (e.g., Boratyński et al, 2017 ; Noakes et al, 2017 ), and the plasticity of performance curves we are suggesting (Figure 1A ). The former serves to maintain body temperatures in variable climates, and the latter optimizes reaction rates when tissue temperatures change despite adjustments of metabolic heat production.…”
Section: Introductionmentioning
confidence: 75%